PERLINDUNGAN HUKUM TERHADAP HAKUBAKU DAN LOGO SELAKU MEREK TERKENAL BERDASARKAN UNDANG-UNDANG MEREK DAN INDIKASI GEOGRAFIS (STUDI PUTUSAN NOMOR 790K/Pdt.Sus-HKI/2020) - Muhammad Faiz Rizqi; R. Rahaditya (Jurnal Hukum Adigama, 2022)
Trademarks are part of Intellectual Property Rights that need to be protected because they containintellectual property that can bring economic benefits to the owner of the trademark rights. Brandprotection is important because brand imitation can occur. Well-known brands become targets forimpersonation. This study aims to determine the protection of well-known brands and the responsibilityof the Directorate General of Intellectual Property Rights as an institution that protects IntellectualProperty Rights. In 2020, there was a well-known trademark dispute between Hakubaku and Logofrom Japan and Hakubaku and Logo which were already registered in Indonesia. Hakubaku and Logofrom Japan are brands that have been used in 2006 and have become well-known brands since 2013.This study focuses on the legal protection of Hakubaku and Logo as well-known brands by analyzingthe Supreme Court Decision Number 790K/Pdt.Sus-HKI/2020 and based on the Trademark LawNumber 20 of 2016 and also the Regulation of the Minister of Law and Human Rights Number 67 of2016. The research method used is the normative research method with the support of additionalinterviews with brand experts and examiners from the Directorate General of IP. The results of thisthesis research that well-known brands need to be protected so that no party imitates the shape of thebrand and logo of a well-known brand. Even though well-known marks have not been registered inIndonesia, they must be protected because Indonesia has ratified the international Trips Agreementand Paris Convention. The responsibility of the Directorate General of IP begins at the time of theadministrative, substantive examination, and until the certificate is issued. The Directorate General ofIntellectual Property Rights also needs to improve inspections so that every application for registrationof a mark does not contain a mark which has elements and similarities in principle with a well-knownmark. If the Directorate General of Intellectual Property Rights carries out its responsibilitiesproperly, then a violation of trademark rights should not occur.